“Proportioning Also is Ancient Turkish”: The Principle of (Geometric) Ratio-Proportion in Ottoman Mosque Architecture - Arif Erdoğan (Sanat Tarihi Yıllığı (Online), 2024)
This study investigates the presence of an art-architectural theory in Ottoman mosques. Due to the insufficiency of historical sources, the aim of this study is to discover the fundamental principle of art and architectural theory, which is the system of ratio-proportion, by utilising sources from the mathematical sciences of the period. The central focus of this research is design theory and continuity in the Edirne Selimiye Mosque, which holds a significant place in the identity of Ottoman architecture. To confirm the validity of this approach, the mosque examples were analysed for temporal and dimensional differences and structural variations. In this context, initially, ratio values in one and two dimensions were determined in the interiors of the mosques. Based on this data, the focus was placed on the sources and approaches related to mathematical sciences (theorical geometry, arithmetic, algebra, and applied geometry) found in the Ottoman palace library, which can be associated with architectural theory,in order to analyse the principles of ratio and proportion. Thus, proving the existence of a fundamental theoretical principle in Ottoman architectural design for the first time, a new perspective has been added to the subject.